Analysis of development of children motor skills - Roman, Kamil (Journal of Education, Health and Sport, 2017)
Movement is an important element of a healthy lifestyle and is needed for every human being. Physical activity is essential especially for children because it ensures proper physical and mental development, good posture and good health. Educating a pre-school child's daily physical activity habits will create the need for an active way of spending leisure time. The purpose of this article is to present ways to support the development of motor skills of a preschool child. This article shows the impact of physical activity on the health of the child.